Explant of an infected four-vessel fenestrated and bilateral iliac branch stent graft in a patient of Jehovah's Witness faith - Carlotta Bugna, MD; Lucas Ruiter Kanamori, MD; Priscila Suguita, MD; Ezra Koh, MD; Thanila A. Macedo, MD; Gustavo S. Oderich, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Infection of fenestrated-branched stent graft is an uncommon but potentially catastrophic complication. The technical challenge of total stent graft explant and reconstruction of the renal-mesenteric arteries is associated with high mortality and morbidity. Among patients of Jehovah Witness faith, refusal to accept blood transfusion adds to the risk given the invasiveness of these operations. We report a Jehovah's Witness faith patient with a recurrent infection of a four-vessel fenestrated and bilateral iliac branch stent graft treated in two stages by axillofemoral bypass, followed by extra-anatomical reconstruction of the mesenteric, renal, and left internal iliac arteries and total stent graft explant and aortic stump closure.